Konsep Pertanian Organik Lahan Kering Melalui Pemanfaatan Budidaya Maggot (Black Soldier Fly) - firmanda, syauqi agung; Samsukdin, Samsukdin (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
Dryland problems are economic and social problems, especially dryland damage caused by imbalances between ecosystems. One solution to achieve ecosystem sustainability in dryland sustainable agriculture is the use of maggot cultivation. The research analysis method used is a descriptive method and qualitative method. The data collected was obtained from primary data through interviews with related parties. Secondary data is obtained from references such as journals, books, and publications of related institutions. The results showed that the maggot life cycle consisted of the Black Soldier Fly (BSF), egg, caterpillar, prepupa, and pupa stages. The utilization of organic waste in all cycles in maggot cultivation is very necessary from the egg stage to the pupa stage. On the other hand, Maggot cultivation produces organic fertilizer that can be used in farming land to increase the productivity of farming land, especially dry land. Broadly speaking, maggot cultivation contributes to and benefits agriculture, especially in economic, social, and ecosystem aspects. Contributions in the economic aspect, namely increasing profits, social aspects, namely being the ability to handle waste on a large scale, and ecosystem aspects, namely maintaining inter-ecosystem sustainability to support sustainable agriculture. Keywords: dryland, maggot, sustainable agriculture